Empowerment of Patani Students through the Islamic Student Association of South Patani Thailand - Habalee Duereh; Irwandi Irwandi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Empowerment is an important aspect of the Thai South Patani student association in Indonesia (PMIPTI). This has a very important influence on Thai South Patani students who come to study in Indonesia because Thai South Patani students need to adapt to their surroundings, especially where Thai South Patani students study. Thus, this organization (PMIPTI) exists as a means to facilitate Thai South Patani students in carrying out their study activities, where this organization (PMIPTI) provides empowerment to students in various fields, including empowerment in the fields of education, ethics, and culture and language. This type of research is a qualitative descriptive analysis in the form of field research using data collection techniques, namely observation, interviews and documentation. Sources of data were obtained from interviews with Thai South Patani students who were educated and joined in the Association of South Patani Thai Islamic Students in Indonesia (PMIPTI) Padang City and there were also taking references from national prosecution (TUNAS), related Islamic history and culture journals with the Development of Thailand's South Patani students. The results of this study concluded that the Empowerment of Patani Students Through the South Thai Patani Islamic Student Association in Indonesia (PMIPTI) Padang City